Peran Guru PKn dalam Meningkatkan Karakter Nasionalisme di Kelas XI SMA Yayasan Perguruan Umum Santosa - Simatupang, Debira Prayunzi; Lahmuddin, Lahmuddin; Amini, Amini (Pancasila and Civics Education Journal (PCEJ), 2025)
ABSTRACTThis article aims to analyze the role of Pancasila and Citizenship Education (PPKn) teachers in developing the nationalistic character of eleventh-grade students at Santosa General Education Foundation Senior High School. This study used a qualitative method with a descriptive approach, through data collection techniques such as interviews, observation, and documentation. The results of the study indicate that PPKn teachers have a strategic role in internalizing nationalistic values through contextual learning planning, the use of participatory methods, and the integration of national issues into classroom discussions. Teachers' exemplary attitudes and behaviors have also been shown to contribute significantly to student character formation. In addition, the use of digital media and creative projects can increase students' interest and understanding of the meaning of nationalism in the global era. Collaboration between teachers and schools in national activities also strengthens the learning environment that supports the formation of nationalistic character. This study confirms that the role of PPKn teachers is very important in developing students' nationalism holistically, although there are still challenges such as low interest among some students and the influence of digital culture. These findings are expected to serve as a reference in developing more effective and adaptive PPKn learning strategies. Keywords: Civics Teacher, Character, Nationalism ABSTRAKArtikel ini bertujuan untuk menganalisis peran guru Pendidikan Pancasila dan Kewarganegaraan (PPKn) dalam meningkatkan karakter nasionalisme siswa kelas XI di SMA Yayasan Perguruan Umum Santosa. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, melalui teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru PPKn memiliki peran strategis dalam menginternalisasi nilai nasionalisme melalui perencanaan pembelajaran yang kontekstual, penggunaan metode partisipatif, serta pengintegrasian isu-isu kebangsaan dalam diskusi kelas. Keteladanan guru dalam sikap dan perilaku juga terbukti berkontribusi signifikan terhadap pembentukan karakter siswa. Selain itu, pemanfaatan media digital dan proyek kreatif mampu meningkatkan minat dan pemahaman siswa tentang makna nasionalisme di era global. Kolaborasi guru dengan sekolah dalam kegiatan kebangsaan turut memperkuat lingkungan belajar yang mendukung pembentukan karakter nasionalis. Penelitian ini menegaskan bahwa peran guru PPKn sangat penting dalam membangun nasionalisme siswa secara holistik, meskipun masih terdapat tantangan seperti rendahnya minat sebagian siswa dan pengaruh budaya digital. Temuan ini diharapkan dapat menjadi rujukan dalam pengembangan strategi pembelajaran PPKn yang lebih efektif dan adaptif.Kata Kunci: Guru PPKn, Karakter, Nasionalisme